Frequency distribution of the methylenetetrahydrofolate reductase polymorphisms in sickle cell hemoglobinopathy-A hospital based study in central India - Suprava Patel; Rachita Nanda; Nighat Hussain; Eli Mohapatra; Pradeep K. Patra (Elsevier, 2021)
Background: Coexistence of polymorphisms of methylenetetrahydrofolate reductase (MTHFR) with sickle cell gene exerts synergistic effect on complications associated with sickle cell hemoglobinopathy. Therefore, the study was planned to determine the frequency distribution of the MTHFR C677T and A1298C genotypes in children diagnosed with sickle cell disease. Methods: A total of 249 children diagnosed with sickle cell anemia, between age group 5-18 years, were enrolled for the cross sectional study. The demographic and clinical details were entered in a structured questionnaire. Collected blood samples were analyzed for hemoglobin and DNA was extracted for genotypic assay for MTHFR C677T and A1298C single nucleotide polymorphisms (SNPs) by Real-time PCR. Results: The study groups comprised of 218 sickle cell trait (SCT) and 31 sickle cell disease (SCD) children. The caste distribution between the two study groups was quite uniform (X231 = 44.21, p = 0.06). Frequencies of homozygous mutants 677TT and 1298CC were 2% and 19.7% respectively. The odds for the variant forms for both SNPs were found to be greater in SCD group. The genotypic and allelic frequencies did not reveal any caste preponderance. The mean age (p = 0.001), weight (p < 0.001), height (p < 0.001), BMI (p < 0.001) and hemoglobin concentrations (p = 0.002) were lower in homozygous 1298CC but not so in 677TT children. A1298C also depicted significant association with BMI and anemia (p < 0.001). Conclusion: Homozygous mutant MTHFR variants would be essential genetic markers especially in children with SCD to identify the vulnerable group who frequently get hospitalized for vascular complications.